Wood and plant-use in 17th-19th century Iceland: archaeobotanical analysis of Reykholt, western Iceland - Zutter, Cynthia (My University, 2000)
As part of a multidisciplinary investigation of post-medieval Icelandic land and plant use practices, archaeobotanical samples were collected from Reykholt, west Iceland in 1988 and 1989. Analyses included plant macrofossils (seeds and leaves) and wood identification from excavated rooms in a 17th century farm house. In conjunction with earlier palaeoentomological studies, the functions of three different excavated rooms are inferred. Archaeobotanical results suggest that the farm was a prosperous one, with imported foodstuffs and wood implements from continental Europe.
Keywords: archaeobotany; plant macrofossils; wood; plant use; Iceland